(untitled) (Bangladesh Journal of Neurosurgery, 2019)
Introduction: Intracranial aneurysms are relatively common, with a prevalence of approximately 4%. Rupture of an intracranial aneurysm (IA) causing subarachnoid haemorrhage (SAH) is a devastating event that is still associated with a 50% case fatality rate, despite major improvements in surgical techniques, diagnosis and interventional treatment. While patient subgroups may clearly qualify for either surgical or endovascular treatment some patients could benefit from multimodal therapy. In this article we will show our team approach experience of management of ruptured intracranial aneurysms. Methods: Cross-sectional descriptive study of 52 patients of ruptured intracranial aneurysm who got admitted into Combined Military Hospital, Dhaka in the period from Jan 2016 to Dec 2018. Patients were evaluated according to their demographic data, analysis of risk factors, radiological location of aneurysms, World Federation of Neurological Surgeon (WFNS) scale, procedural options for aneurysm treatment, post procedural complications. We excluded unruptured cases and those patients who were treated conservatively. General outcome was assessed through the Glasgow out-come (GOS) scale. Data analysis was done by using computer software SPSS version 25.0. Patients studied were mainly middle-aged with mean age 44 ±5.2 years and predominantly female. Most of the patients had previous history of hypertension 45 (86.53%). WFNS scale 2 was observed in 34 (65.38%). Anterior communicating (Acom) artery aneurysm was more frequent which is found in 16 (30.77%) cases. 37 (71.15%) patients underwent microsurgical clipping whereas 13 (25%) patients underwent endovascular intervention and 2 (3.85%) patients needed combined approach. Complications were more in microsurgical clipping group 38 (73.08%) in comparison to endovascular group 13 (25%). GOS scale 5 was observed in 30 (57.70%) cases. Conclusion: Our experience of management of ruptured intracranial aneurysms together with their outcome have been reflected in this small study. For better outcome of ruptured intracranial aneurysms decision can be made on an individual case by case basis. Hybrid treatment option of staged endovascular and open microsurgical proceduresare sometimes needed as a combined approach. Bang. J Neurosurgery 2019; 9(1): 39-43